PEMAHAMAN NILAI PENDIDIKAN MULTIKULTURAL DALAM UPAYA MEMBANGUN KEBERAGAMAAN INKLUSIF SANTRI PADA PESANTREN MODERN DATOK SULAIMAN - Abdullah Sappe Ampin Maja (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
This research explain about how to apprehends multicultural value’s in Islamic Boarding School Datok Sulaiman Palopo. The main problem’s in this thesis are, how teacher’s apprehension about multicultural educations and what theirs effort to applicate this values in learning process of boarding area beyond formal and non formal studies. This research, writer used qualitative descriptive approach, namely Library Research and Field researches. Subject in this research were principal, teacher, student’s. collecting data was used are observation, interview, and documentation. The investigation of data used cross check technique and descriptive analysis.The result of this research, shows some of important conclusion’s, in the education field, Islamic boarding school Datok Sulaiman Palopo was difficult saw that this institution is modern. The system are combination between traditionally and modern. The people of Pesantren seem take foundation al-muhafadhotu ‘ala qadimi al-salih wa al-akhdu bi jadidi al-aslah (The maintain old something that is considered have good value’s and take a new something for kindness) as standing on. Therefore, bandongan and sorogan learning models as a traditionally system can be apply with classical system as modern characteristic. In thinking, in fact- principle, teacher in the learning processes formal and non formal have appreheanded and practice multicultural value’s in boarding area. Key Words : Multicultural Values, Inclusive, Students Religiousness